Aspects of bull reproduction with emphasis on cattle in Ethiopia. I. Sexual Development and onset of puberty - Tegegne, Azage; Kassa, T.; Mukasa-Mugerwa, E. (Ethiopian Society of Animal Production, 1995)
Although the importance of bull reproduction in enhancing genetic progress and influencing cow herd fertility has long been recognized in many parts of the world, there has been very little attention paid to bulls in Ethiopia. Proper management of young bulls aims to improve growth rate so that they produce good quality semen at the earliest age possible. Early onset of puberty in breeding bulls could reduce generation interval and enhance genetic progress. The importance of early onset of puberty in genetically superior bulls through proper early growth and Development can not be overemphasized. In this paper, the physiological aspects of sexual Development and onset of puberty in the young bulls are presented. Factors of importance, mainly genotype differences and nutritional effects are discussed and available data on bull reproduction in the tropics with emphasis on bulls in Ethiopia are collated and presented. Data from Bos taurus and other Bos indicus breeds are also included for comparative information and in areas where information on bulls in tropical environments and in Ethiopia is not available. Areas of future research in young bull reproduction and management for enhancing genetic progress and improving herd fertility under both natural mating and artificial insemination management conditions are also presented.